Aplikasi Pengenalan Bibit Sayuran Organik Dan Bibit Sayuran Hidroponik Dengan Adobe Flash - Annisa, Syara; Harahap, Herlina; Asih, Munjiat Setiani (Jurnal Ilmu Komputer dan Sistem Komputer Terapan (JIKSTRA), 2022)
Vegetables have many kinds that are consumed by the community, ranging from organic vegetables and hydroponic vegetables. Organic and hydroponic vegetables have significant differences in cultivation as well as different planting media so that the vegetables produced by organic and hydroponic seeds are also different, namely organic vegetable seeds with soil media and hydroponic vegetables with growing media that contain more nutrients. Therefore, an introduction application design for organic vegetable seeds and hydroponic vegetable seeds was designed using Adobe Flash CS6. The application aims to help the community to distinguish between organic vegetable seeds and hydroponic vegetables that they want to grow so that the vegetables planted have treatment according to the procedure and the media. There is material about the definition, planting media, shape & structure, types of vegetables, the benefits of vegetables and the advantages & disadvantages of organic vegetables and hydroponic vegetables. This research method uses a qualitative method which is carried out by observing organic and hydroponic seeds, as well as collecting data in the cultivation of organic vegetables and hydroponic vegetables.